(untitled) (Global Journal of Science Frontier Research, 2025)
A visible cosmos is no larger than a grain of sand suspended within a decaying gravitational shell. Nested black holes containing entire cosmic structures. These are not metaphors, but the physical implications of the Dead Universe Theory (DUT) - a novel cosmological model proposing that our observable universe is a localized energetic anomaly formed not from a hot singularity but from the internal collapse of a far older, colder, and darker superstructure: the Dead Universe. In this framework, what we perceive as " the universe" is embedded within a structural black hole, composed of exotic second-layer dark matter - a gravitational topology- unlike anything described by classical cosmology. Unlike the Schwarzschild-type singular ities predicted by general relativity, these structural black holes do not form from stellar collapse but from the internal thermodynamic decomposition of an ancestral cosmos trillions of times larger than our own. The DUT proposes that the observable universe is not expanding, but retracting - dissolving asymmetrically from the edges inward, driven by entropy, not inflation. This paradigm offers gravitational and thermodynamic coherence while avoiding the speculative mechanisms of multiple theories, wormholes, and exotic inflation fields. It interprets the cosmological red shift, cold spots in the cosmic microwave background, and the early appearance o f super massive black holes not as anomalies but as expected consequences of a collapsing background structure.